Relationship Between Spousal Support And Exclusive Breastfeeding In Mothers Of 0-6 Month Old Infant - Novita Andriani Br. Manjorang; Srilina Pinem; Arihta Br Sembiring; Marta Armita Br Silaban; Anita Sari; Grace Laura Fidelia (Indonesian Journal Publisher, 2026)
Background: Breast milk is the best life-giving fluid that is essential for babies up to 6 months of age because it has the most complete and ideal nutritional composition for the growth and development of babies, which can meet their nutritional needs during the first 6 months. However, only 39 percent of all babies in the world are exclusively breastfed. Breastfeeding is a natural process, but many mothers are still unable to breastfeed or stop breastfeeding early. Many reasons are cited by mothers who do not breastfeed their babies, including being busy with work, fear of gaining weight, and insufficient milk production (Damanik, 2020). A study proved that husband’s support was an important aspect of exclusive breastfeeding (DelCoreetal. 2018). Purpose: To determine correlation between husband’s support and exclusive breastfeeding mothers at Siti Hajar Clinic Medan Marelan. Methods: The type of research used was quantitative with a cross sectional approach. The study population consisted of 30 mothers who were breastfeeding their children aged 0-6 months at husband’s exclusive breastfeeding assistance center at Siti Hajar Clinic od Medan Marelan. Data analyisis using chi-square. Results: From a survey of 30 breastfeeding mothers, 83.3% of respondents were suppored by their husband’s and 16.7% were not supported by their husband’s. 100% of mothers brestfeed their babies exclusively. This, it means that the p-value = 0.000, p-value <0.05 between the husband’s support for exclusive breastfeeding. Conclusion: Based on the research, it can be seen that there was correlation between husband’s support for exclusive breastfeeding and the behavior of the husband’s to spport, encourage and support the practice of ecxlusive breastfeeding for mothers during breastfeeding.